FOXFIRE LIVING : DESIGN, RECIPES & STORIES FROM THE MAGICAL INN IN THE CATSKILLS - Clark, Eliza, 1963-; Trojian, Tim; Wray, Arden (New York : Harper Design, an imprint of HarperCollins Publishers, 2019)
"A gorgeous field guide to the innovative vintage design style that is the hallmark of Foxfire Mountain House, the magical inn in the Catskills, with design ideas, recipes, projects, and tips from proprietors Eliza Clark and Tim Trojian, for achieving its dreamy, rustic modern style in your own home"-- Provided by publisher.
Includes bibliographical references.
Keywords: Foxfire Mountain House (Hotel); Decoration and ornament, Rustic -- New York (State) -- Catskill Mountains